Bullying victimization, suicidal behavior, and help-seeking in Chinese adolescents: a legal-psychological Study of resilience and responsibility - Ge, Xianyun (Frontiers in Psychology, 2025)
Bullying victimization is a significant public health concern among adolescents, with profound psychological and behavioral consequences. Grounded in an ecological and ethical framework, this study connects psychological mechanisms with the moral and institutional responsibilities involved in protecting adolescents’ wellbeing. It examines the associations between bullying victimization, suicidal behavior, help-seeking attitudes, and resilient coping among a sample of 987 middle school students (aged 12–15) in China. Additionally, it explores the mediating roles of peer support and core self-evaluations in these associations. Data were analyzed using SmartPLS with the PROCESS module. The results indicate that bullying victimization is positively associated with suicidal behavior, and negatively associated with help-seeking attitudes and resilient coping. Core self-evaluations significantly mediate the associations between bullying victimization and both help-seeking attitudes and resilient coping, highlighting the importance of self-perceptions in mitigating adverse effects. Peer support, while positively related to help-seeking attitudes and resilient coping, did not significantly mediate the association between bullying victimization and suicidal behavior. These findings suggest that individual psychological resources play a crucial role in shaping adolescents’ responses to bullying, while social support alone may not be sufficient to buffer the risk of suicidality. The study underscores the need for multi-level and culturally sensitive interventions, integrating school-based mental health programs, counseling services, and family support initiatives to strengthen resilience and promote help-seeking among adolescents.